2012
DOI: 10.1007/s11738-012-1088-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osmotic stress on physiological and biochemical characteristics in drought-susceptible and drought-resistant wheat genotypes

Abstract: In this study, the seedlings of two wheat cultivars were used: drought-resistant Chinese Spring (CS) and drought-susceptible (SQ1). Seedlings were subjected to osmotic stress in order to assess the differences in response to drought stress between resistant and susceptible genotype. The aim of the experiment was to evaluate the changes in physiological and biochemical characteristics and to establish the optimum osmotic stress level in which differences in drought resistance between the genotypes could be reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
72
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(93 citation statements)
references
References 53 publications
19
72
0
2
Order By: Relevance
“…This data is in agreement with the results obtained in our previous experiment [33]. Supplementing SA or ABA to the medium (PEG + SA or PEG + ABA) caused a decrease of these seedling parameters for both cultivars.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This data is in agreement with the results obtained in our previous experiment [33]. Supplementing SA or ABA to the medium (PEG + SA or PEG + ABA) caused a decrease of these seedling parameters for both cultivars.…”
Section: Resultssupporting
confidence: 93%
“…It was shown that the optimal level of osmotic stress—defined as most suitable for differentiating drought resistance of SQ1 and CS wheat cultivars based on the differences in the response to osmotic stress caused by PEG—was −0.75 MPa [33]. Osmotic stress was found to affect water status, seedlings morphology, gas exchange parameters, chlorophyll content, osmotic potential, lipid peroxidation, water soluble sugars and proline contents in drought resistant and drought susceptible wheat cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…The parental forms differ in tolerance to drought and present diverse physiological responses and yields. These characteristics were previously confirmed in earlier studies [23,25,26].…”
Section: Plant Materialssupporting
confidence: 86%
“…Plants can avoid the damage brought about by drought through several mechanisms such as compatible solutes accumulation (Marci nska et al, 2013). Organic solutes can accumulate to high level without disturbing intracellular biochemistry, protecting sub-cellular structures, mitigating oxidative damage caused by free radicals and maintaining the enzyme activities under different environmental stress conditions (Hanson et al, 1977;Hanson and Nelsen, 1978;Ashraf and Foolad, 2007;Marci nska et al, 2013;Talaat andShawky, 2013, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Organic solutes can accumulate to high level without disturbing intracellular biochemistry, protecting sub-cellular structures, mitigating oxidative damage caused by free radicals and maintaining the enzyme activities under different environmental stress conditions (Hanson et al, 1977;Hanson and Nelsen, 1978;Ashraf and Foolad, 2007;Marci nska et al, 2013;Talaat andShawky, 2013, 2014a). Furthermore, during drought stress excessive generation of reactive oxygen species (ROS) such as superoxide radical (O 2 ROS and maintain redox homeostasis, plants have developed a well-integrated antioxidant defense system, which is made up of antioxidant molecules and antioxidant enzymes such as superoxide dismutase, catalase, and enzymes involved in the ascorbateglutathione cycle (Mittler, 2002).…”
Section: Introductionmentioning
confidence: 99%